2007
DOI: 10.1007/s11468-007-9030-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Enhancement at a Liquid–Metal–Liquid Interface

Abstract: Herein, we report the first experimental demonstration of surface plasmon enhancement at a liquid-metalliquid interface using a pseudo-Kretschmann geometry. Pumping gold nanoparticle clusters at the interface of a pxylene-water mixture, we were able to measure a fluorescence enhancement of three orders of magnitude in Rose Bengal at an excitation wavelength of 532 nm. The observed increase is due to the local electric field enhancement and the reduction of the fluorescence lifetime of dye molecules in the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…It has been shown that methanol injection is an effective way to induce the formation of a monolayer film with a metallic reflectance visible by eye when using citrate-stabilized Au NPs [18], as shown in Fig. 2b.…”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that methanol injection is an effective way to induce the formation of a monolayer film with a metallic reflectance visible by eye when using citrate-stabilized Au NPs [18], as shown in Fig. 2b.…”
Section: Resultsmentioning
confidence: 97%
“…The enhancement was attributed to the electric field enhancement in the plasmonic hot-spots and the reduction of the fluorescence lifetime of dye molecules in close vicinity to the metal surface. 156 θ SPR is the angle of the incident light hitting the interfacial gold nanofilm that leads to a minimum (or dip) in reflectance at a specific wavelength. Also using a pseudo-Kretschmann configuration (see Figure 9A(i)), Hojeij et al produced clear experimental evidence of the dip in reflectance beyond the critical angle due to SPR absorption by the interfacial gold nanofilm, closely matching theoretical calculations; 89 see Figure 9A(ii) and (iii).…”
Section: Optical Reflectivity and Scatteringmentioning
confidence: 99%
“…Gold nanorods (GNRs) are highly suitable plasmonic nanomaterials for the large third-order nonlinear response resulting from the surface plasmons resonance (SPR) characteristics [14]- [20]. Surface plasmons (SPs) refer to the electromagnetic oscillations generated by the excitation of a free electron and an electromagnetic field in a metal surface region under an external electromagnetic field [21], [22]. Because of the spherical symmetry of the gold nanoparticles, free electrons oscillate uniformly in all directions, so there is only one SPR band [23].…”
Section: Introductionmentioning
confidence: 99%